Free Spectra of Equivalential Algebras with Conjunction on Dense Elements - Przybyło, Sławomir; Słomczyńska, Katarzyna (Bulletin of the Section of Logic, 2024)
We construct free algebras in the variety generated by the equivalential algebra with conjunction on dense elements and compute the formula for the free spectrum of this variety. Moreover, we describe the decomposition of free algebras into directly indecomposable factors.